Penyuluhan Pengolahan Limbah Pertambangan Emas Rakyat di Desa Lopok, Kabupaten Sumbawa - Suhadi Suhadi; Sueb Sueb; Vivi Novianti; Murni Sapta Sari; Kiswojo Kiswojo; Muhammad Syamsussabri; Endang Lasminawati (Jurnal Pengabdian Kepada Masyarakat, 2023)
Lopok Village, Lopok District in Sumbawa Regency, West Nusa Tenggara Province is one of the sub-districts with a large majority of artisanal miners. The people's gold mining in this area is a small-scale mining that uses amalgamation and cyanidation methods in gold processing. This activity is widely carried out due to the nature of the gold ore which is very suitable for processing using amalgamation and cyanidation techniques. The purpose of implementing this service is to provide counseling on processing gold mining waste. The implementation method is carried out by providing interactive materials and discussions. This activity was carried out in Lopok Village with 85 participants. The location of the direct service is carried out at the people's gold mining location at four points. In the service that has been carried out, there are several activities carried out to increase public understanding and awareness of the issue of community mining, namely counseling to Miners, Stakeholders, and the General Public.